Alpheus chilensis Coutiere in Lenz 1902 - D'Acoz, Cédric D'Udekem; Degrave, Sammy (Zenodo, 2018)
Alpheus chilensis Coutière in Lenz, 1902 Widely distributed from the Galápagos Islands southwards throughout Peru and Chile as far south as the Puerto Montt area (Lenz 1902, as Alpheus maindroni Coutière, 1902 and Alpheus bouvieri var. chilensis Holthuis 1952); intertidal and very shallow subtidal. Published as part of D'Acoz, Cédric D'Udekem & Degrave, Sammy, 2018, A new genus and species of large-bodied caridean shrimp from the Crozet Islands, Southern Ocean (Crustacea, Decapoda, Lipkiidae) with a checklist of Antarctic and sub-Antarctic shrimps, pp. 201-240 in Zootaxa 4392 (2) on page 222, DOI:10.11646/zootaxa.4392.2.1, http://zenodo.org/record/1195302